2010
DOI: 10.1097/ccm.0b013e3181eb3c51
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist in patients recovering spontaneous breathing after acute respiratory distress syndrome: Physiological evaluation*

Abstract: Compared to pressure-support ventilation, neurally adjusted ventilatory assist in acute respiratory distress syndrome patients holds promise for limiting the risk of overassistance, preventing patient-ventilator asynchrony, and improving overall patient-ventilator interactions. Neural triggering (neurally adjusted ventilatory assist-electrical activity of the diaphragm) considerably decreased patient-ventilator asynchrony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 36 publications
(38 reference statements)
8
96
1
10
Order By: Relevance
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18).…”
Section: Nava In Infantssupporting
confidence: 75%
See 1 more Smart Citation
“…These results are in line with studies in adults that all reported similar synchrony improvement with NAVA (5,11,12,20,21). In the pediatric population, no study has yet quantified the trigger delays and cycling-off delays during conventional ventilation and during NAVA, although two feasibility studies have demonstrated that during NAVA, at least two-thirds of assisted breaths were triggered by the neural signal (17,18).…”
Section: Nava In Infantssupporting
confidence: 75%
“…Numerous studies have shown that NAVA efficiently unloads the respiratory muscles (8,9) and delivers more synchronous ventilation than PSV (5,(9)(10)(11)(12). Furthermore, it was shown that ventilator pressures (during NAVA) follow the natural variability in breathing pattern (13)(14)(15).…”
mentioning
confidence: 99%
“…However, when delivering PS-NIV through a helmet, neural triggering has been shown to improve patient-ventilator synchrony compared to pneumatic triggering [11]. As neurally adjusted ventilatory assist (NAVA) [12] uses a neural signal (the diaphragm electrical activity, or EAdi, independent from airway pressure and flow signals), to trigger and cycle-off the ventilator as well as to adapt the amount of pressure delivered, and as NAVA improves patient-ventilator interaction during invasive ventilation [13][14][15][16], we hypothesized that NAVA could improve patient-ventilator synchrony during NIV. The purpose of this study was to test this hypothesis in adult intensive care patients requiring NIV because of acute respiratory failure or because of being at risk of respiratory failure after extubation [3].…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, the pressure level is determined by the neural output of the patient's central respiratory command, which would be expected to prevent over-assistance. [12][13][14][15] Moreover, recent studies suggest that NAVA may allow a high level of breathing pattern variability. [16][17] Avoiding overassistance and delivering proportional assistance would be expected to limit apneas, although ventilation varies less during the night than during the day.…”
Section: See the Related Editorial On Page 884mentioning
confidence: 99%